Rosa Luxenbourg et sa doctrine : la révolution russe - Luxemburg, Rosa; Rubak, Simon; Sabatier, Patrick; Jaquier, Maurice; Lefeuvre, René (Paris : Spartacus, 1977)
Bibliotheek François Vercammen
Frans
Monografie